2020
DOI: 10.1108/jsm-10-2019-0376
|View full text |Cite
|
Sign up to set email alerts
|

How perceptions of firm environmental and social values influence frontline employee outcomes

Abstract: Purpose More than ever, consideration of the natural environment and social welfare are values that firms must signal to their stakeholders. One way to do this is by adopting an environmental orientation (EO) and pro-social organizational identity (PSOI). The purpose of this paper is to examine how frontline employees (FLEs) respond to these firm-level values through four outcomes. Design/methodology/approach Polynomial structural equation modeling with response surface analysis was implemented on FLEs surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…The difference lies in the type of information. While market-oriented firms use intelligence about general customer preferences, competitive strategies, and market analytics to produce favorable firm outcomes, firms with a strong EO use environment-specific information, or green market intelligence, to influence similar outcomes ranging from environmental and economic performance (Gabler et al, 2020a) to sales performance and word-of-mouth (Gabler et al, 2020b). This means these firms factor a stakeholder into their decision-making that was not originally part of market orientation, namely, the natural environment.…”
Section: Market Orientation and Sustainable Supply Chainsmentioning
confidence: 99%
“…The difference lies in the type of information. While market-oriented firms use intelligence about general customer preferences, competitive strategies, and market analytics to produce favorable firm outcomes, firms with a strong EO use environment-specific information, or green market intelligence, to influence similar outcomes ranging from environmental and economic performance (Gabler et al, 2020a) to sales performance and word-of-mouth (Gabler et al, 2020b). This means these firms factor a stakeholder into their decision-making that was not originally part of market orientation, namely, the natural environment.…”
Section: Market Orientation and Sustainable Supply Chainsmentioning
confidence: 99%
“…These inflection points result in curvilinear graphs, which pinpoint optimal levels of the inputs on associated outcomes. TMGT logic has been used to model interactions ranging from the impact of firmlevel orientations on the frontline (Gabler et al, 2020) to how service climate influences employee satisfaction and performance (Gabler et al, 2017). Crick (2019) examines how managers can balance cooperation and competition to find the optimal level of company performance.…”
Section: Eco-social Orientationmentioning
confidence: 99%
“…Specifically, when firms overinvest in multiple strategic orientations, they may experience diminishing returns. Past research has shown that when a firm juggles multiple goals, it may cause a distraction from goals more imperative to firm success such as sales performance (Gabler et al, 2020). In this case, when both SO and EO are simultaneously high, the firm may be overextending its resources, distracting managers from investing in resources that produce economic returns.…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, their skepticism prompts them to seek more information about environmentally friendly products, which can lead to negative word-of-mouth (WOM) (Leonidou and Skarmeas, 2017). Further and most important to the context of this study, underlying company values are often not seen through corporate mission statements or sustainability webpages but interactions with frontline employees (Gabler et al , 2020).…”
Section: Introductionmentioning
confidence: 99%